Synthesizing one-part geopolymers from rice husk ash. (15th October 2016) - Sturm, P.; Gluth, G.J.G.; Brouwers, H.J.H.; Kühne, H.-C.
Abstract: One-part geopolymers offer advantages over conventional geopolymers with regard to handling and storage of feedstocks. However, they often suffer from a low degree of reaction, a high amount of crystalline byproducts, and consequently low strength. In this study, one-part geopolymers were produced from rice husk ash (RHA) and sodium aluminate, and investigated by XRD, ATR-FTIR, SEM and compressive strength testing. The compressive strength of the material was ∼30 MPa, i.e. significantly higher than for comparable one-part geopolymers. This is attributed to an almost complete reaction of the RHA and the absence of crystalline byproducts (zeolites) in the hardened geopolymer.